Axially Chiral Dibenzazepinones by a Palladium(0)‐Catalyzed Atropo‐enantioselective C−H Arylation. (23rd July 2018) - Newton, Christopher G.; Braconi, Elena; Kuziola, Jennifer; Wodrich, Matthew D.; Cramer, Nicolai
Abstract: Atropo‐enantioselective C−H functionalization reactions are largely limited to the dynamic kinetic resolution of biaryl substrates through the introduction of steric bulk proximal to the axis of chirality. Reported herein is a highly atropo‐enantioselective palladium(0)‐catalyzed methodology that forges the axis of chirality during the C−H functionalization process, enabling the synthesis of axially chiral dibenzazepinones. Computational investigations support experimentally determined racemization barriers, while also indicating C−H functionalization proceeds by an enantio‐determining CMD to yield configurationally stable eight‐membered palladacycles.